THE EFFECT OF CITICOLIN IN MOTORIC IMPROVEMENT OF ACUTE ISCHEMIC STROKE PATIENTS IN SITI KHODIJAH SEPANJANG HOSPITAL - Dza’wan Maula Iwanatud Diana; Laily Irfana; Yelvi Levani; Uning Marlina (Jurnal Ilmu Kesehatan dan Kesehatan, 2020)
Background: According to WHO, stroke is the leading cause of morbidity and the second cause of death with a mortality rate of around 5.54 million. Stroke, based on its etiology, consists of ischemic and hemorrhagic. Ischemic stroke is caused by a blockage in the blood-brain, whereas hemorrhagic stroke occurs due to the rupture of brain blood vessels. Based on the pathophysiology of ischemic stroke, its therapy consists of thrombolytic in thrombus for brain reperfusion and anticoagulants or antiplatelet in strokes due to embolization because it is grown in a collateral-containing lavatory and neuroprotectant assistance to trace cytotoxic nerves. Neuroprotectants that are often used are piracetam and citicoline. Citicoline improves neuronal cell membranes by increasing synthesis of the main component of cell membranes, phosphatidylcholine, then repaired neuronal cell membranes. Objective: To find out motor improvement in stroke patients at Siti Khodijah Sepanjang Hospital by giving 500mg of citicoline per day orally for 5 days. Methods: A case-control observational analytic study using medical record data. Consists of a group with standard therapy, antiplatelets, and another group with 500mg/day antiplatelet and citicoline therapy for 5 days. Patients were examined for MRC motor on the first day and the fifth day. Results: The statistical test used the Chi-Square test  and wilcoxon test with a significance value of 0.00 and 0,01 (<0.05). Conclusion: obtained significant motor improvement in stroke patients 500mg/day for 5 days at Siti Khodijah Sepanjang Hospital.   Latar belakang: Menurut WHO stroke menjadi penyebab utama morbiditas dan sebab kematian nomor dua dengan angka kematian sekitar 5,54 juta. Stroke berdasarkan etiologinya diklasifikasikan menjadi stroke iskemik dan stroke hemoragik. Stroke iskemik merupakan stroke yang diakibatkan oleh adanya sumbatan pada pembuluh darah di otak sedangkan stroke hemoragik akibat adanya pecahnya pebuluh darah otak. Berdasarkan patofisiologinya terapi stroke iskemik terdiri dari trombolitik pada iskemik akibat trombus untuk reperfusi otak dan antikoagulan atau antiplatelet pada stroke akibat emboli sebagai pencegahan terbentuknya trombus pada pembuluh darah kolateral serta pemberian neuroprotektan untuk menghambat penyebaran kerusakan neuroglia pada penumbra akibat proses sitotoksik. Neuroprotektan yang sering digunakan adalah pirasetam dan citicolin. citicolin berfungsi memperbaiki membran sel neuron dengan meningkatkan sintesis komponen utama membran sel yaitu phosphatidylcholine sehingga terjadi peningkatan perbaikan membran sel neuron. Tujuan: Untuk mengetahui perbaikan motorik pada pasien stroke iskemik akut di RS Siti Khodijah Sepanjang. Metode: Jenis penelitian analitik observasional case-control bersifat retrospektif menggunakan data rekam medis. Terdiri dari kelompok dengan terapi standar yaitu antiplatelet dan kelompok lain dengan terapi antiplatelet dan citicolin 500mg/hari selama 5 hari. Pasien dilakukan pemeriksan motorik MRC di hari pertama dan hari kelima. Hasil: Uji statistik menggunakan uji Chi-Square dan uji wilcoxon dengan nilai signifikansi masing-masing 0,00 dan 0,01 (<0,05). Kesimpulan: didapatkan perbaikan motorik yang signifikan pada pasien stroke iskemik akut dengan pemberian citicoline 500mg/hari selama 5 hari di Rumah Sakit Siti Khodijah Sepanjang.